2002
DOI: 10.1021/ac0202536
|View full text |Cite
|
Sign up to set email alerts
|

Optical Chloride Sensor Based on Dimer−Monomer Equilibrium of Indium(III) Octaethylporphyrin in Polymeric Film

Abstract: A novel transduction chemistry for preparing optical anion-selective polymeric films that respond reversibly and selectively to chloride ion activity is demonstrated. The chloride sensors are prepared by casting thin (5-10 microm) plasticized PVC films containing indium(III) octaethylporphyrin hydroxide, along with optimized levels of a lipophilic tetraphenylborate salt, onto glass slides. When bathed in low-pH buffered solutions void of chloride, the porphyrin species spontaneously forms a hydroxide ion-bridg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 39 publications
1
63
1
Order By: Relevance
“…This was observed when a 1:1 molar ratio of each compound was present (Fig. 2) [24][25][26], this was not observed in the present studies.…”
Section: Porphyrin As Charged Ionophorecontrasting
confidence: 67%
“…This was observed when a 1:1 molar ratio of each compound was present (Fig. 2) [24][25][26], this was not observed in the present studies.…”
Section: Porphyrin As Charged Ionophorecontrasting
confidence: 67%
“…It is well known that most membrane electrodes based on metalloporhyrin ionophores have significant response to hydroxide ions [28,29]. Hydroxide has a great affinity to the metal ion center of examined metalloporphyrins (logK F-,OH-= 6.6, 6.9, 7.0 and 7.5 for electrodes 1, 9, 14 and 22 respectively) replacing the counterion of metalloporphyrin when in contact with water [30].…”
Section: The Influence Of Ph On Electrodes Parametersmentioning
confidence: 99%
“…It has been reported that other group 13 metalloporphyrins (Ga(III) and In(III)) form hydroxy-bridged dimer species [32], and that selective cleavage of these dimers by analyte ions (F À for Ga(III) and Cl À for In(III)) is responsible for the observed non-Nernstian behavior. [33] Indeed, such dimer - monomer chemistry has already been employed to construct optical sensors for chloride [34] and gaseous amines [35] since the dimeric and monomeric forms of the porphyrins exhibit significant differences in their l max for UV-Vis absorption. For the aluminum(III) porphyrin systems reported here, membrane electrodes equilibrated and conditioned with 10 mM fluoride (added to the internal solution, electrodes VIII and XII) display near-Nernstian fluoride response (see Fig.…”
Section: Potentiometric Response Characteristics Of Membrane Electrodmentioning
confidence: 99%